Pusat Kebudayaan Tionghoa Bagansiapiapi Dengan Pendekatan Arsitektur Kontemporer - Parlinggoman Pasaribu; Mira Dharma Susilawaty; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Chinese cultures are still implemented and applied in Bagansiapiapi as an expression of worship and gratitude to the ancestors. These chinese festivals are celebrated in Bagansiapiapi cause the culture and history of Chinese are known by the local people, both in domestic and abroad. But the problems are the supporting facilities and the places to accommodate these activities are in a low number. Because of that, Chinese Cultural Center in Bagansiapiapi need a building as the activities center that focuses on Chinese culture and to support cultural facilities, to make sure people known about Chinese history, where pedigree is from, and the culture. This research used contemporary architecture approach which suited by the present time, and the Chinese architectural buildings will be able to reflect the contemporary Chinese building without losing the characteristics of the building itself. Through the concept of "Lion Dance" or as known as Barongsai, the building can demonstrate the movement patterns of the Barongsai itself. It also used the Chinese elements including the use of a courtyard, emphasis on the shape of the roof, open structural elements, and the use of colors on the buildings.keywords: Chinese Culture Center, Bagansiapiapi, Contemporary Architecture